S.P.R.I.N.T. San Pedro revitalized and integrated - Malbog, Diana Camille P.
This thesis study focuses on San Pedro City, Laguna as the chosen neighborhood to be analyzed and designed with an architectural intervention that will help promote the identified agenda for the city. San Pedro is now becoming a bustling city which is known to be the Gateway to Manila. Having around 300,000 residents, most of which working in Metro Manila according to the Comprehensive Land Use Program of San Pedro City, authored by Palafox Associates, the city became a very viable source of income for transport companies. Scattered around the cities are these transport companies. They are making their presence known because of the traffic generated by the additional volume and congestion on certain points of the city where these transport companies are abutting the roads. The situation is worsened by the existing transport system of the city - only having informal stops and stations for most modes of transport. In line with this transport agenda, this thesis study aims to improve the transport system of San Pedro City through an architectural intervention that can promote an organized transport system, with a design that is currently studied in other countries, that can significantly help in making a faster circulation and transfer of modes, faster boarding and alighting times, and with pedestrianized and better wayfinding. In general, the design process is by revitalizing and integrating the different modes of transport terminals of around the chosen site in San Pedro City, Laguna.